OPEN SOURCE SOFTWARE AND INTELLECTUAL PROPERTY - Nedelkovski, Boris (E-Journal VFU, 2024)
This paper explores the connection between open source software (OSS) andintellectual property (IP), analysing different topics such as patents, copyright, licensing andlegal disputed. It delves into different types of open source licenses, focusing on the permissiveand copyleft licenses, and analyses their effect on software developers. Furthermore, this paperdebates the adoption of open source software by companies and how it coexists with theirintellectual property policies. Major legal cases such as SCO Group vs. IBM, Oracle America,Inc. v. Google LLC, and Jacobsen v. Katzer are analysed and examined with the goal ofillustrating the major intellectual property issues in the open source community. The paperhighlights the importance of contributor license agreements (CLAs), license compliance andlegal education in guaranteeing effectiveness in management of open source projects andconflict resolution. Lastly, the content puts an accent on the importance of enforcementinstruments and collaboration in the software community in the direction of promotingtransparency, growth and efficiency of open source software.